ANTECEDENTS OF SUSTAINABLE COMPETITIVE ADVANTAGE IN MICRO, SMALL AND MEDIUM ENTERPRISES - Erni Widajanti; Mulyanto Nugroho (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study intends to investigate the elements that influence the Sustainable Competitive Advantage of micro, small and medium enterprises (MSMEs). This study focuses on the 1.211 culinary MSMEs registered with the Surakarta City Cooperatives and MSMEs Office in 2020. Samples were gathered from as many as 301 respondents, but only 282 respondents met the standards for data analysis. Method of data analysis utilizing SEM-AMOS. According to the findings of the study, Supply Chain Management, Information Technology Capability, and Innovation have a positive and significant effect on a company’s sustainable Competitive Advantage. The findings of this study are expected to be utilized by culinary MSMEs’ in Surakarta to develop or enhance competitive advantage. It is anticipated that the findings of this study will also contribute to science, particularly in the development of competitive MSMEs